Three-dimensional kinematic analysis of the golf swing using instantaneous screw axis theory, Part 2: golf swing kinematic sequence - Vena, A.; Budney, D.; Forest, T.; Carey, J. P. (Sports Engineering, 2011)
Recent studies have measured body segment rotation to study the kinematic sequence of the downswing. However, this sequence has yet to be determined relative to an instantaneous screw axis (ISA), free to change position and orientation during motion to reflect shifts in a segment`s dominant axis of rotation. In Part 2 of this two-part study, the objectives were to compute the amplitude of segment angular velocity relative to the corresponding ISA of that segment and verify if the magnitude of segment angular velocity followed the proximal to distal sequence of the summation of speeds principle. Results indicate that the kinematic sequence of 2 of the 5 subjects analyzed supports the summation of speeds principle, where the sequence in which the maximum angular velocity about the pelvis, shoulders and left arm occurred, for one subject, at 68.2 ± 3.2, 72.8 ± 1.7 and 100 ± 0.0% of the downswing.